2012
DOI: 10.1002/jsfa.5649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal processing and various chemical substances on formaldehyde and dimethylamine formation in squid Dosidicus gigas

Abstract: Non-enzymatic decomposition of TMAO was a key pathway during the thermal processing of jumbo squid, and Fe(2+) was a crucial activator in the formation of FA and DMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Reduction rate of formaldehyde increased because the number of active molecules of polyphenols and formaldehyde increased due to high temperature. Zhu et al reported that formaldehyde levels was significantly increased in the supernatant of jumbo squid with the increase of heating temperature [11].In our work found that the higher temperature was beneficial to the reaction of polyphenols with formaldehyde, so blueberry leaf polyphenols can also capture more formaldehyde in the squids at high temperature, and decreased formaldehyde content in the squids. In practical application, we should select high temperature in the proper range.…”
Section: Effect Of Temperature On Reactivity Of Polyphenols With Formsupporting
confidence: 59%
“…Reduction rate of formaldehyde increased because the number of active molecules of polyphenols and formaldehyde increased due to high temperature. Zhu et al reported that formaldehyde levels was significantly increased in the supernatant of jumbo squid with the increase of heating temperature [11].In our work found that the higher temperature was beneficial to the reaction of polyphenols with formaldehyde, so blueberry leaf polyphenols can also capture more formaldehyde in the squids at high temperature, and decreased formaldehyde content in the squids. In practical application, we should select high temperature in the proper range.…”
Section: Effect Of Temperature On Reactivity Of Polyphenols With Formsupporting
confidence: 59%
“…Significant reduction of FA levels were observed in all treatments and all fish samples when compared with fresh fish (9.4-32.6 mg/kg, dipped in 1h water (5.3-12.8 mg/kg), dipped in 1h 5% brine (3.8-11.4 mg/kg), fried fish (0.9-2.6 mg/kg), boiled fish (0.6-1.6 mg/kg), cooked fish (0.7-2.3 mg/kg), boiled fish water (0.6-1.6 mg/kg) and fish gravy (0.7-2.5 mg/kg). The non-enzymatic FA formation was dependent on heating temperature and time (Zhu et al, 2012). They found that accelerated formation of FA and DMA in jumbo squid at pH 6-7.…”
Section: Impact Of Different Treatment Methods On Fa In Fish and Seafoodmentioning
confidence: 99%
“…The result showed that high temperature processing promoted the conversion of TMAO to FA, and FA content increased with the temperature. A pH of about 6 -7 accelerated the degradation of TMAO to FA, as well as Fe 2+ alone or Fe 2+ combined with cysteine and ascorbate promoted the formation of FA [19]. Spinelli et al reported the Cys with Fe 2+ or hemoglobin could also catalyze decomposition of TMAO to FA and DMA [20].…”
Section: Generation Mechanism Of Endogenous Fa In Aquatic Productsmentioning
confidence: 99%